The Application of Tactical Approaches in Learning Handballs - Didik Rilastiyo Budi; Rohman Hidayat; Ayu Rizky Febriani (JUARA : Jurnal Olahraga, 2019)
The tactical approach needs to be applied in the learning of the hand ball because it makes students move actively during learning, so far the approach used by the teacher is still in the conventional way so that the tactical approach can be one of the new breakthroughs in physical education learning in school. The purpose of the study was to find out whether the tactical approach model could be an alternative problem solving so that students could master the basic techniques of handball in high school Lembang. The research method uses Classroom Action Research. The study sample was a class X student of high school Lembang. The research instrument uses basic technical tests and the skills of playing bola tangan. Analysis of data using the Norm Reference Reference. The results showed students experienced an increase in learning outcomes from cycle I with a good percentage of 26.7%, cycle II 33.3% and cycle III by 36.7%, this happened because with a tactical approach students could get more opportunities to perform basic technical skills in the game handball The conclusion of this study is that a tactical approach can make it easier for students to overcome difficulties in playing handball.